2020
DOI: 10.2147/tacg.s210325
|View full text |Cite
|
Sign up to set email alerts
|

<p>Alternating Hemiplegia of Childhood: Understanding the Genotype–Phenotype Relationship of ATP1A3 Variations</p>

Abstract: Alternating hemiplegia of childhood (AHC) is a rare neurological disorder affecting children with an onset before 18 months. Diagnostic clues include transient episodes of hemiplegia alternating in the laterality or quadriparesis, nystagmus and other paroxysmal attacks as tonic and dystonic spells. Epilepsy is also a common feature. In the past, a great effort has been done to understand the genetic basis of the disease leading to the discovery of mutations in the ATP1A3 gene encoding for the alpha3 subunit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 88 publications
2
31
0
Order By: Relevance
“…Moreover, some pathogenic variants have been reported to manifest different phenotypes in non-related cases as well as intrafamilial. In view of the available evidence, we agree with authors that have proposed to consider ATP1A3 -related disorders as a clinical continuum rather than distinct entities, with an age-dependent pattern of emergence and progression of different signs and symptoms ( 11 ). For example, being EE in the most severe extreme and RDP in the milder.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, some pathogenic variants have been reported to manifest different phenotypes in non-related cases as well as intrafamilial. In view of the available evidence, we agree with authors that have proposed to consider ATP1A3 -related disorders as a clinical continuum rather than distinct entities, with an age-dependent pattern of emergence and progression of different signs and symptoms ( 11 ). For example, being EE in the most severe extreme and RDP in the milder.…”
Section: Discussionsupporting
confidence: 89%
“…The causative role of ATP1A3 variants in the pathogenesis of several neurological disorders with a similar pattern of inheritance has been previously documented in several reviews ( 8 11 ). Here we have performed an up-to-date review of this topic, including several novel recently reported phenotypes in ATP1A3 pathogenic variant carriers.…”
Section: Introductionsupporting
confidence: 57%
“…Although an increasing number of pathogenic variants have been described, the variants listed above have been found to cause about 60% of all cases in the most extensive cohort studies. In particular, the p.Asp801Asn variant accounts for 30-43% of all cases, p.Glu815Lys 16-35% of cases, and p.Gly947Arg 8-15% (25). No other genes occasionally related to AHC patients (21)(22)(23)(24) were detected in this case series.…”
Section: Discussionmentioning
confidence: 64%
“…Disease-modifying therapy does not exist, albeit several drugs are administered as prophylaxis for paroxysmal attacks. The most frequent drugs used in AHC are flunarizine, benzodiazepines, carbamazepine, barbiturates, and valproic acid (25). It has been widely demonstrated that flunarizine induces a significant improvement in dystonic and plegic episodes (26).…”
Section: Introductionmentioning
confidence: 99%
“…21) Alternating hemiplegia is associated with ATP1A3 gene mutation, which encodes the α3 subunit of Na + /K + ATPase. 22) Some PNE like breath-holding spells (BHS) might be linked to iron. Iron is known to play an important role as a co-factor in neurotransmitter synthesis and myelin formation, affecting…”
Section: Pathophysiologymentioning
confidence: 99%